Flow Experience 2016
DOI: 10.1007/978-3-319-28634-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Running and Flow: Does Controlled Running Lead to Flow-States? Testing the Transient Hypofontality Theory

Abstract: This chapter presents a summary of three studies, using treadmill running in a laboratory context, measuring fl ow-states via self-report data. To situate the theoretical context of the studies, Dietrich's (Conscious Cogn 12:231-256, 2003). Transient Hypofrontality Theory (THT) is outlined, to show that fl ow-states are theorized in this work as being as a result of a down-regulated prefrontal cortex. Also, other neuropsychological research into fl ow is summarized to build the justifi cation of our three proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The premise behind this simplification appears to be that when attention is wholly invested in and directed toward a task, action and awareness merge in the absence of spare attention, and self-related thoughts and monitoring of experiential factors (such as reflective self-consciousness) fade from awareness (Csikszentmihalyi, 2014b;Nakamura & Csikszentmihalyi, 2002;Pelet et al, 2017). Interestingly, part of the support for this absorption theme came from a branch of neuroscientific research, in which it was suggested that flow occurrence results in a depleting "onion-peeling" effect of higher cognitive processes (e.g., Stoll & Pithan, 2016;Ulrich et al, 2016b). During flow, it is argued by some that the highest layers of consciousness -those that include higher cognitive functions (i.e., self-reflective thinking and time monitoring)-are most susceptible to change when alterations to mental states occur and resources are reallocated (Stoll & Pithan, 2016).…”
Section: The Flow Experience Dimension 1: Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The premise behind this simplification appears to be that when attention is wholly invested in and directed toward a task, action and awareness merge in the absence of spare attention, and self-related thoughts and monitoring of experiential factors (such as reflective self-consciousness) fade from awareness (Csikszentmihalyi, 2014b;Nakamura & Csikszentmihalyi, 2002;Pelet et al, 2017). Interestingly, part of the support for this absorption theme came from a branch of neuroscientific research, in which it was suggested that flow occurrence results in a depleting "onion-peeling" effect of higher cognitive processes (e.g., Stoll & Pithan, 2016;Ulrich et al, 2016b). During flow, it is argued by some that the highest layers of consciousness -those that include higher cognitive functions (i.e., self-reflective thinking and time monitoring)-are most susceptible to change when alterations to mental states occur and resources are reallocated (Stoll & Pithan, 2016).…”
Section: The Flow Experience Dimension 1: Absorptionmentioning
confidence: 99%
“…Specifically, our aim in this review was to describe the consistency (and inconsistency) in constructs, dimensions, and working definitions utilized to describe flow, and to chart the varied antecedents, measurement instruments, and outcomes utilized when operationalizing flow. In line with recommendations for cross-disciplinary approaches, and calls to understand flow phenomenologically, cognitively, neurologically, physiologically, socially, and behaviorally (Beard, 2015;Csikszentmihalyi, 2014b;Kawabata & Mallett, 2016;Marr, 2001;Peifer, 2012;Rich, 2013;Stoll & Pithan, 2016), a secondary aim (if possible) was to highlight any common findings that could be used and operationalized across scientific disciplines.…”
mentioning
confidence: 99%
“…Dietrich and Stoll (2010) argue that sports are particularly good at engendering flow states for two reasons. First, bodily motion is extremely complex in computational terms, and as such uses considerable mental resources (demonstrated by Stoll & Pithan, 2016). When prolonged, this is sufficient to divert processing away from non-critical cognitive processing (i.e.…”
Section: Automaticitymentioning
confidence: 99%
“…There was found to be no reduction in frontal activity, suggesting that a general mechanism of hypofrontality may be overly simplistic. Support for hypofrontality comes mainly from studies finding reductions in cognitive function as a result of prolonged exercise (see Stoll & Pithan, 2016). Whether this state is representative of a general flow mechanism is questionable.…”
Section: Automaticitymentioning
confidence: 99%
“…Evidence, however, speaks to the opposite and suggests that people can enjoy life better and have more optimal experiences when they reduce excessive cognition (Kaiser, 2019;Norman, 2020). Less metacognition can reduce an individual's inner critic, which may produce a more relaxed state, allowing for increased creativity and life optimization (Stoll & Pithan, 2016;Swann et al, 2017). This process of silencing the inner critic is called transient hypofrontality, and it occurs when the prefrontal cortex of the brain slows in activity and high-level thinking decreases (Sinnett et al, 2020).…”
Section: Definition Of Flow Statementioning
confidence: 99%